Gendered career expectations in context : the relevance of normative and comparative reference groups - Beckmann, Janina [Verfasser] (My University, 2021)
"Although women are increasingly entering male-dominated careers, they remain strongly underrepresented in science, technology, engineering and mathematics (STEM) occupations. While previous explanations emphasize the importance of individual preferences or family socialization, less is known about how the school context contributes to these differences. This study aimed to examine the role of the classroom context as a frame of reference for students’ career expectations, focusing on comparative and normative reference group effects. Building on gender socialization theory and rational choice models, I investigate whether these contextual effects affect students’ occupational expectations in a gender-specific way. Drawing on a large representative sample of secondary school students in Germany, I find that the gender gap in students’ occupational expectations is larger in classrooms characterized by a high mathematical confidence and high aspirations toward STEM. In classrooms with a pronounced STEM-related classroom climate, female students less frequently expect to work in a STEM career, while for male students the same classroom climate is associated with higher expectations toward STEM. More generally, this study demonstrates that research on the explanation of gender differences in career expectations profits from incorporating social context effects within schools and classrooms." (author's abstract ; BIBB-Doku)
Keywords: G 2.4.5 Gender Mainstreaming; P 1.3 Frauen; 370; 300; Geschlechterforschung; Geschlechtersegregation; geschlechtsspezifische Sozialisation; Frauen; Berufserfahrung; Stereotyp; Sekundarbereich